High-Novelty-Preference Rats are Predisposed to Compulsive Cocaine Self-administration - Belin, David (Nature Publishing Group, 2011)
Sensation/novelty-seeking is amongst the best markers of cocaine addiction in humans. However, its implication in the vulnerability to cocaine addiction is still a matter of debate, as it is unclear whether this trait precedes or follows the development of addiction. Sensation/novelty-seeking trait has been identified in rats on the basis of either novelty-induced locomotor activity (high-responder (HR) trait) or novelty-induced place preference (high-novelty-preference trait (HNP)). HR and HNP traits have been associated with differential sensitivity to psychostimulants. However, it has recently been demonstrated that HR rats do not develop compulsive cocaine self-administration (SA) after protracted exposure to the drug, thereby suggesting that at least one dimension of sensation/novelty seeking in the rat is dissociable from the vulnerability to switch from controlled to compulsive cocaine SA. We therefore investigated whether HNP, as measured as the propensity to choose a new environment in a free choice procedure, as opposed to novelty-induced locomotor activity, predicts the vulnerability to, and the severity of, addiction-like behavior for cocaine. For this, we identified HR/LR rats and HNP/LNP rats before any exposure to cocaine. After 60 days of cocaine SA, each rat was given an addiction score based on three addiction-like behaviors (persistence of responding when the drug is signaled as not available, high breakpoint under progressive ratio schedule and resistance to punishment) that resemble the clinical features of drug addiction, namely inability to refrain from drug seeking, high motivation for the drug and compulsive drug use despite adverse consequences. We show that, as opposed to HR rats, HNP rats represent a sub-population predisposed to compulsive cocaine intake, displaying higher addiction scores than LNP rats. This study thereby provides new insights into the factors predisposing to cocaine addiction, supporting the hypothesis that addiction is sustained by two vulnerable phenotypes: a ‘drug use prone' phenotype such as HR which brings an individual to develop drug use and an ‘addiction prone' phenotype, such as HNP, which facilitates the shift from sustained to compulsive drug intake and addiction.